2015
DOI: 10.1016/j.bbr.2014.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral responses and role of the prefrontal cortex in conditioned pain modulation: an fMRI study in healthy subjects

Abstract: The mechanisms underlying conditioned pain modulation (CPM) are multifaceted. We searched for a link between individual differences in prefrontal cortex activity during multi-trial heterotopic noxious cold conditioning and modulation of the cerebral response to phasic heat pain. In 24 healthy female subjects, we conditioned laser heat stimuli to the left hand by applying alternatively ice-cold or lukewarm compresses to the right foot. We compared pain ratings with cerebral fMRI BOLD responses. We also analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 57 publications
4
57
0
3
Order By: Relevance
“…In these regions and the amygdala, signal intensity changes were positively correlated to CPM analgesia; that is, greater signal intensity increases were associated with reduced CPM analgesia. Although previous investigations also reported CPM‐related changes most of these brain regions, they did not report changes in the dlPFC or PCC [Bogdanov et al, ; Brock et al, ; Davis, ; Moont et al, ; Piche et al, ; Song et al, ; Sprenger et al, ]. There are a number of reasons that may account for the differences including the fact that we used considerably more subjects in our investigation (54 versus 10–22 subjects in previous studies) and, importantly, divided our subjects into two groups corresponding to whether or not individual subjects displayed a CPM response and found that only about half of our subjects displayed CPM analgesia.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In these regions and the amygdala, signal intensity changes were positively correlated to CPM analgesia; that is, greater signal intensity increases were associated with reduced CPM analgesia. Although previous investigations also reported CPM‐related changes most of these brain regions, they did not report changes in the dlPFC or PCC [Bogdanov et al, ; Brock et al, ; Davis, ; Moont et al, ; Piche et al, ; Song et al, ; Sprenger et al, ]. There are a number of reasons that may account for the differences including the fact that we used considerably more subjects in our investigation (54 versus 10–22 subjects in previous studies) and, importantly, divided our subjects into two groups corresponding to whether or not individual subjects displayed a CPM response and found that only about half of our subjects displayed CPM analgesia.…”
Section: Discussionmentioning
confidence: 84%
“…Although previous studies have reported CPM‐related activity changes in regions such as the cingulate and prefrontal cortices, they did not investigate differences in brain activation patterns in those that did compared to those that did not express CPM analgesia; furthermore, they did not assess the influence of these cortical regions on brainstem sites responsible for CPM such as the SRD [Bogdanov et al, ; Piche et al, ; Sprenger et al, ]. This is important if we are to understand why some individuals display CPM analgesia and others do not and whether an alteration in brain circuitry predisposes an individual to developing chronic pain following injury.…”
Section: Introductionmentioning
confidence: 99%
“…by modulating activity of medial frontal cortex areas involved in the control of the affective and cognitive dimensions of pain. These areas play indeed a paramount role in individual levels of central pain modulation in healthy subjects (54) and are dysfunctioning in chronic migraine (49), medication overuse headache (55) and chronic cluster headache (48). They are modulated both by transcutaneous and percutaneous pericranial nerve stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…The strength of the PAG resting functional connectivity can explain some of the normal variability in CPM; higher resting connectivity between the PAG and cortical pain processing regions correlates with greater CPM efficacy (Harper et al, 2018). CPM scores are also correlated with the modulation of the laser-induced BOLD response in left posterior insula/SII (Bogdanov et al, 2015). …”
Section: How Does It Work? the Originsmentioning
confidence: 99%